Circulating Ubiquitous RNA, A Highly Predictive and Prognostic Biomarker in Hospitalized Coronavirus Disease 2019 (COVID-19) Patients. (11th December 2021) - Bruneau, Thomas; Wack, Maxime; Poulet, Geoffroy; Robillard, Nicolas; Philippe, Aurélien; Puig, Pierre Laurent; Bélec, Laurent; Hadjadj, Jérôme; Xiao, Wenjin; Kallberg, Julia Linnea; Kernéis, Solen; Diehl, Jean Luc; et al.
Abstract: Background: Approximately 15–30% of hospitalized coronavirus disease 2019 (COVID-19) patients develop acute respiratory distress syndrome, systemic tissue injury, and/or multi-organ failure leading to death in around 45% of cases. There is a clear need for biomarkers that quantify tissue injury, predict clinical outcomes, and guide the clinical management of hospitalized COVID-19 patients. Methods: We herein report the quantification by droplet-based digital polymerase chain reaction (ddPCR) of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNAemia and the plasmatic release of a ubiquitous human intracellular marker, the ribonuclease P (RNase P) in order to evaluate tissue injury and cell lysis in the plasma of 139 COVID-19 hospitalized patients at admission. Results: We confirmed that SARS-CoV-2 RNAemia was associated with clinical severity of COVID-19 patients. In addition, we showed that plasmatic RNase P RNAemia at admission was also highly correlated with disease severity ( P  < .001) and invasive mechanical ventilation status ( P  < .001) but not with pulmonary severity. Altogether, these results indicate a consequent cell lysis process in severe and critical patients but not systematically due to lung cell death. Finally, the plasmatic RNase P RNA value was also significantly associated with overall survival. Conclusions: Viral and ubiquitous blood biomarkers monitored by ddPCR could be useful for the clinical monitoring and the management of hospitalized COVID-19 patients. Moreover, these results could pave the way for new and more personalized circulating biomarkers in COVID-19, and more generally in infectious diseases, specific from each patient organ injury profile. Abstract : Blood biomarkers for the clinical monitoring and the management of hospitalized coronavirus disease 2019 (COVID-19) patients are clearly needed. Herein, we report the particular usefulness of ubiquitous circulating RNA monitoring by droplet-based digital polymerase chain reaction (ddPCR) as a predictive and prognosis biomarker for hospitalized COVID19 patients.